Interpretasi Lapisan Bawah Permukaan Tanah Menggunakan Metode Geolistrik 2-D (Mapping) - Nugroho, S A; Railasha, Vergiane; Satibi, Syawal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Research was conducted at a location in Pekanbaru city. On this location has two test line at a distance from each other as far as 3 m, which for each testing line will be tested by using 2D geoelectric Wenner and dipole-dipole arrays then performed data processing by software Res2dinv. In addition, there will be handbor and laboratory testing for the soil in depth 1, 2, and 3 m to determine the soil classifications. And then, this result will be compared or matched with geoelectric result. Generally, the geoelectric (soil resistivity) results from the both arrays is sufficient to represent the actual potention of underground conditions. That can be evidenced with have suitability result between geoelectric, handbor, and laboratory test. In this result, Wenner array gives better result than dipole-dipole array. Wenner array gives resistivity range more closer and layers of the soil are easier to interpret than dipole-dipole array.Keywords: Resistivity, Geoelectric, Wenner, dipole-dipole